2011
DOI: 10.1002/jcp.22528
|View full text |Cite
|
Sign up to set email alerts
|

Carotid body function and ventilatory responses in intermittent hypoxia. evidence for anomalous brainstem integration of arterial chemoreceptor input

Abstract: Obstructive sleep apnea is a frequent medical condition consisting in repetitive sleep-related episodes of upper airways obstruction and concurrent events of arterial blood hypoxia. To this condition there is a frequent association of cardiovascular and other pathologies conforming the obstructive sleep apnea syndrome (OSAS). Laboratory models of OSAS consist in animals exposed repetitive episodes of Intermittent hypoxia (IH) which also develop cardiovascular pathology, mostly hypertension. The overall OSAS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 53 publications
1
38
0
12
Order By: Relevance
“…This has been linked to sensitization of the arterial chemoreflex (15,32,45,50,67), which results from a complex mixture of mechanisms ranging from increased O 2 sensitivity of carotid body chemoreceptors (11,21,30,31,50) to enhanced sympathoexcitatory neurotransmission through the brain stem arterial chemoreflex arc (10,18,38,50,67). However, emerging evidence indicates that persistent neurogenic CIH hypertension involves additional adaptive mechanisms that contribute to heightened sympathetic drive.…”
Section: Discussionmentioning
confidence: 99%
“…This has been linked to sensitization of the arterial chemoreflex (15,32,45,50,67), which results from a complex mixture of mechanisms ranging from increased O 2 sensitivity of carotid body chemoreceptors (11,21,30,31,50) to enhanced sympathoexcitatory neurotransmission through the brain stem arterial chemoreflex arc (10,18,38,50,67). However, emerging evidence indicates that persistent neurogenic CIH hypertension involves additional adaptive mechanisms that contribute to heightened sympathetic drive.…”
Section: Discussionmentioning
confidence: 99%
“…General procedures used to label chemoreceptor cells 3 H-catecholamine ( 3 H-CA) (CA) deposits and later to study their release have been described in previous publications (Vicario et al 2000 ;Gonzalez-Martín et al 2011 ). And analytical methods have been described in detail in Conde et al ( 2006 ).…”
Section: H-ca) Release Experiments Using Freshly Isolated Intact Cbsmentioning
confidence: 99%
“…The chemoreflex is thought to play an important role [20, 26, 27, 97101], although other mechanisms may contribute, as described below. Animal studies have indicated that the peripheral chemoreceptors located in the carotid body play a pivotal role in the response to hypoxia seen in OSA [102109]. More recent analyses have demonstrated differential expressions of the various Hypoxia Inducible Factor (HIF) subtypes in the carotid body associated with local inflammation [110112].…”
Section: Introductionmentioning
confidence: 99%